Drivers overtaking cyclists in the real-world: Evidence from a naturalistic driving study. (November 2019) - Kovaceva, Jordanka; Nero, Gustav; Bärgman, Jonas; Dozza, Marco
Highlights: Naturalistic driving data provide valuable information about how car drivers overtake cyclists. Drivers' comfort zone boundaries are quantified from the naturalistic UDRIVE data. Factors car speed, manoeuvre type, presence of oncoming traffic, and driver characteristics are investigated. Drivers were significantly closer to the cyclist when an oncoming vehicle was present. Abstract: The total number of road crashes in Europe is decreasing, but the number of crashes involving cyclists is not decreasing at the same rate. When cars and bicycles share the same lane, cars typically need to overtake them, creating dangerous conflicts—especially on rural roads, where cars travel much faster than bicycles. During these manoeuvres, drivers try to minimize risk in the complex traffic environment by staying in their comfort zone while overtaking the cyclist. This study quantified drivers' comfort zone boundaries (CZBs) and investigated the combination of factors that affect the CZBs while drivers overtake cyclists in a naturalistic setting. The results show that the higher the car speed the larger the CZBs while approaching and passing, but the presence of an oncoming vehicle significantly decreased the CZB during passing. The drivers' age, gender, and Arnett Inventory of Sensation Seeking score were not found to have a statistically significant impact on the CZBs. The findings of this study provide implications for the design of road safety intervention programs that increase safety for all road users and the development of advanced driver-assistance systems that could interact with cyclists.